The Effectiveness of the Flipped Classroom Approach Over Traditional Teaching for a Comprehensive Understanding of Embryology by the First-Year MBBS Professionals - Shreevastava, Amit K; Das, Rajat S; Kailash, Balkund (Curēus (Palo Alto, CA), 2025)
IntroductionThis study compared the effectiveness of the flipped classroom model with traditional teaching methods in improving embryology understanding among first-year MBBS students in competency-based medical education. The goal was to foster a deep understanding of the subject and produce well-rounded medical professionals who can contribute to the healthcare sector.Materials and methodsThe study involved first-year medical undergraduates. Traditional teaching was used for five months initially, followed by the flipped classroom approach for the subsequent five months. Post-tests followed each session, with a Likert scale feedback survey involving students and faculty in the anatomy department yielding insightful results.ResultsPost-test scores in the flipped classroom (6.54 ± 0.87) significantly surpassed those of traditional teaching (5.94 ± 0.78) (P = 0.001). Chi-square testing revealed a noteworthy difference in post-test scores category favoring the flipped classroom (P = 0.002). Additionally, cognitive assessment demonstrated the flipped classroom's superiority in knowledge, application, and analysis (P = 0.01, P = 0.01, P = 0.003, respectively). Feedback indicated the flipped classroom's efficacy in enhancing competency, with students excelling in embryology topics. Overall, students and faculty members perceive integrating the flipped classroom into the curriculum positively. This strengthens the fact that the model is more effective than traditional teaching methods in improving embryology comprehension among first-year MBBS students.ConclusionThe findings suggest that implementing this method can improve students' knowledge, application, and analytical skills in every subject. These results have positive implications for medical education, reinforcing knowledge acquisition with far better understanding and thus enhancing the analytical skills for efficient application.